A novel method for predicting superior gluteal nerve safe zones in the lateral approach to the hip. Issue 4 (12th March 2020) - Piponov, Hristo; Osmani, Feroz A.; Parekh, Amit; Brooker, Jay M.; Abraham, Edward; Hussain, Awais K.; Patetta, Michael J.; Gonzalez, Mark H.
Abstract: Introduction: The superior gluteal nerve (SGN) is at risk for laceration during lateral approach total hip arthroplasty (THA). The purpose of this study is to assess the accuracy of the trochanter‐to‐iliac crest distance (TCD) and the nerve‐to‐trochanter distance (NTD) ratio in determining a reproducible safe zone around the SGN independent of height. Materials and Methods: Eighteen hemipelvises were dissected and the SGNs were exposed. The distance (NTD) from greater trochanter (GT) to the most inferior branch of the SGN encountered in each of the three approaches (Bauer et al., 1979) was measured. A reference distance (TCD) was measured from the GT to the highest point on the iliac crest. The NTD was divided by the TCD to generate standardized ratios. Coefficient of variation CV = ( SD /mean) × 100 was calculated for each distance and ratio to measure relative variability. Results: The standardized ratios (and CV) were determined for the nerve branches in three different surgical approaches: Hardinge 0.464 (0.9%), Bauer 0.406 (1.7%), and Frndak 0.338 (4.1%). There was a strong correlation of the individual NTDs with the TCD: NTD for Hardinge ( r = 0.996, p < .001), NTD for Bauer ( r = 0.984, p < .001), and NTD for Frndak ( r = 0.932, p < .001). Conclusion: By measuring the TCD preoperatively and using the respective standardized ratios, surgeons can accurately predict the NTD and how proximal to the GT each SGN branch can be expected to be encountered during lateral approach to the hip. This will allow surgeons to work with a more precise safe zone around the SGN and minimize the possibility for a nerve injury.